The Impact of Earnings Management on the Relationship Between Operating Cash Flows and Stock Returns On Jordanian Public Shareholding Industrial - al-Olimat, Nofan; AL-hashash, Bara’ah (The Arab Journal of Administration, 2022)
This study aimed to identify the impact of earnings management on the relationship between operating cash flows and stock returns in Jordanian public shareholding industrial companies, to achieve the objective of the study, the analytical descriptive approach was used, the study population is composed of all the Jordanian public shareholding industrial companies Listed on the Amman Stock Exchange, the financial period (2013-2017) of (52) companies, in the study community the modified jones model was used to measure the earnings management practices, and to analyze the study data (E-views) to answer the hypotheses of the study were used analysis of variance test (ANOVA). The results revealed that there was an Impact of operating cash flows on stock returns, while there is no Impact of earning management in the relationship between operating cash flows and stock returns, there is no impact earnings management on stock returns. The most important recommendation of the study is to invite the Jordanian public shareholding industrial companies to follow the methods and strategies to generating cash flow operational, there by contributing to enhancing their capacity to meet their obligations, and maintain its survival and continuity.